TO PERIODIC RECURRENT FRACTIONS OF THIRD DEGREE - Семенчук, Андрій Васильович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Periodic recurrent fractions of third degree are investigated by means of parapermanents of triangular matrices.